(untitled) (Orfeu, 2024)
This article aims to identify and characterize aspects of the art and work of women in the world of Rio de Janeiro’s music between the years 1889 and 1902. Starting from a thought-provoking text, a 1914 chronicle by Lima Barreto about the situation of musical creation in Brazil of his time, we developed a critique and an analysis of the main argument of his text to achieve the proposed objective. To support the criticism and carry out the research, we researched documents in periodicals of the time, between the years 1889 and 1902 (with the upper limit a little larger than our time frame), in the Digital Hemeroteca of the National Digital Library from Brazil in order to be able to, supported by sources, reconstruct some aspects of women’s performance in different areas of the Rio’s world of music. We present evidence of the presence and circulation of women musicians, performers and creators. We register conductors and composers who had works announced and published for presentation, performance and sale in their time. We argue, in chorus with other research on the relationship between women and music in Brazil at that period, that they remained excluded from history.